How workplace incivility leads to work alienation: A moderated mediation model - Xia, Bingnan; Wang, Xiaochen; Li, Qing; He, Yuzhen; Wang, Wei (Frontiers in Psychology, 2022)
Workplace incivility remains a prevailing issue and has significant potential for harmful consequences. This study aims to investigate the influencing mechanism of workplace incivility on work alienation from the perspective of targets. Based on the social exchange theory, our research examines the role of interpersonal trust as a mediator along with the moderator of career resilience in the said association. Through a two-wave-time-lagged quantitative research design, a sample of 315 nurses from China was investigated with questionnaires on workplace incivility, work alienation, interpersonal trust, and career resilience. The results indicated that workplace incivility was positively related to work alienation with interpersonal trust as a mediator. Workplace incivility caused a decline in interpersonal trust, which led to work alienation. Career resilience buffered such an impact. High career resilience weakened the association linking workplace incivility to interpersonal trust. Organizations should pay more attention to workplace incivility and consider empowering nurses’ career resilience, which could alleviate the negative impact of workplace incivility.